Variational Transition State Theory and Tunneling Calculations with Reorientation of the Generalized Transition States for Methyl Cation Transfer - González-Lafont, Angels; Villà, Jordi; Lluch, José M; Bertrán, Juan; Steckler, Rozeanne; Truhlar, Donald G (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 1998)
The new RODS algorithm based on optimizing the orientation of the dividing suface at each point along the reaction path in order to maximize the free energy of the generalized transition state containing that point has been used to carry out variational transition state calculations and tunneling calculations for two reactions with high-frequency vibrations strongly coupled to the reaction coordinate, (Cl-)(CH3NH3 +) → ClCH3(NH3) and ClCH3 + NH3, and CH3Cl(H2O) + NH3(H2O) → (CH3NH3 +)(Cl-)(H2O)2. These reactions, both of which involve the transfer of a methyl cation between Cl- and NH3, show much larger variational-transition-state and tunneling effects than were observed in previous studies of the transfer of methyl cations between anionic centers. However, they are hard to study because the adiabatic potential energy curves of both reactions and, as a consequence, the corresponding free energy of activation profiles show big dips when the minimum energy path (MEP) is followed using standard methods, even when very small step sizes are taken to compute the steepest-descent path. The application of RODS methodology eliminates those dips, giving rise to smooth free energy of activation profiles and vibrationally adiabatic potential curves. Calculations of variational rate constants and tunneling effects are significantly improved.